Peranan Pendidikan Dalam Menghindari Pergaulan Bebas Anak Usia Remaja - Dewi Ajnaliyah; Rizky Fitra Satria; Ferianto Martinus; Arnol Darius Bulu; Yohanes Lamatewulu; Alexsandro Irmino Djata Wulu; Diah Ayu Sanggarwati (PUTRA JAWA PUBLISHER, 2023)
The promiscuity of juvenile delinquents is alarmingly increasing. This paper examines the role of education in preventing promiscuity in teenagers. Education plays a crucial role in character building, which guides teenagers to make right choices and avoid wrong ones. The development of character is instrumental in determining whether adolescents can effectively navigate diverse situations, particularly in avoiding promiscuity. Alongside promoting gender-sensitive education, providing equal opportunities for women can lead to improved protection, services, and welfare for vulnerable women who are the most disadvantaged in cases of adolescent promiscuity.